Intercropping of Summer Onion with Mukhikachu (Bangladesh Agronomy Journal, 2025)
An experiment was conducted at the research field of Regional Agricultural Research Station (RARS), Bangladesh Agricultural Research Institute (BARI), Cumilla during Kharif I, 2022 to find out the suitable combination of onion with mukhikachu for increasing total productivity, economic return and maximize land utilization through intercropping system. Seven treatments viz., i) Sole mukhikachu ii) Two rows of summer onion in between two rows of mukhikachu iii) Three rows of summer onion in between two rows of mukhikachu iv) Two rows of summer onion in between two double rows of mukhikachu v) Three rows of summer onion in between two double rows of mukhikachu vi) Sole summer onion. The trial was set up in a randomized complete block design with three replications. The unit plot size was 3.0 m × 2.70 m. The mukhikachu was (Var. BARI Mukhikachu-1) a main crop and onion (Var. BARI Peaz-5) were used as intercrops in the study. The sole crop of mukhikachu was planted at a spacing of 60 cm × 45 cm, the sole crop of onion at a spacing of 15 cm × 10 cm. Results showed that, different intercropping combination significantly influenced yield and yield contributing characters of mukhikachu. The yield of mukhikachu was comparatively lower in intercropping than sole mukhikachu but total productivity was increased due to additional yield of onion. Increased total productivity in terms of mukhikachu equivalent yield (MEY) was 38.72-42.28 t ha−1 in intercrop combination compared to sole mukhikachu 31.70 t ha−1 (main crop). All the intercropping combinations showed better performance in terms of mukhikachu equivalent yield, gross return and benefit cost ratio (BCR) over sole crops. Among the intercropping combinations three rows of onion in between two double rows of mukhikachu was the most feasible intercropping system in respect of mukhikachu equivalent yield (42.28 t ha−1), gross return (Tk.8,45600), gross margin (Tk. 5,18100) and benefit cost ratio (2.58). Three rows of summer onion in between two rows of mukhikachu (BCR 2.56) and two rows of summer onion in between two double rows of mukhikachu (BCR 2.51) were also feasible intercrop combination.Bangladesh Agron. J. 2025, 28(1): 29-34